Effect of Sound Preference on Loudness Tolerance and Preferred Listening Levels Using Personal Listening Devices - Yula C. Serpanos; Thomas DiBlasi; Jasmin Butler (Audiology Research, 2025)
Background/Objectives: This study examined the effect of sound preference on loudness tolerance (LTLs) and preferred listening levels (PLLs) using personal listening devices (PLDs). The implication of this relationship on hearing health promotion counseling and practices using PLDs is discussed. Methods: Participants were 50 individuals, aged 21 to 90 years, with normal hearing or hearing loss. Listeners rated several sound samples (i.e., music, running speech, and machinery noise) played through a PLD using earphones according to their sound preference (i.e., enjoyable, acceptable, and unpleasant) and then self-adjusted the volume setting to their LTL and PLL for a sound sample in each sound preference category. Results: Most listeners judged music (70%) as enjoyable, running speech (54%) as acceptable, and machinery noise (84%) as unpleasant. No significant differences were found in LTLs according to sound preference, but PLLs for enjoyable sounds occurred at significantly higher levels compared with those deemed acceptable or unpleasant. Conclusions: Listeners using PLDs perceived LTLs and PLLs differently according to their sound preferences. PLLs occurred at significantly higher volumes for sounds deemed enjoyable when using PLDs. The implication is that hearing health counseling should include information to PLD users on the potential of altered loudness perception with enjoyable sounds, which may lead to higher and riskier PLD listening levels.